IDENTIFIKASI KUTUKEBUL DAN PEMBUATAN KUNCI IDENTIFIKASI DALAM BENTUK PORTABLE DOCUMENT FORMAT (PDF) - Istia Siti Amalia; Wahyu D. Natawigena; Martua S. Sianipar; Ichsan Nurul Bari (UIN Sunan Gunung Djati Bandung, 2023)
Whiteflies Aleurodicus dispersus and Bemisia tabaci are major pest on several horticultural crops because of their feeding activity which absorbs fluids through the phloem. They are also Geminivirus vectors. Whiteflies reduce yield crop around 30%-100% on high attack. Whiteflies have morphological variety that affect feeding and reproduction behaviour in certain host plant. Identification was carried out on the puparium shape because of phenotype variations depend on the physical character of the leaf surface. This research aimed to study differences the morphology of whiteflies puparium in several plants and to create an identification key in PDF format. This research used the literature study method from textbooks and published national and international journal. The samples were taken from Bandung Regency and West Bandung Regency, West Java on tomatoes, chayote, peanuts, and beans. Then puparium was prepared in a microscope slides-mounted and morphological identification was carried out. The result obtained are subdorsum of A. dispersus has compound pores and thorax without tracheal comb. Lingula is very long, usually extending past the vasiform orifice and has two pairs of setae at the end. While the puparium of B. tabaci has lobe-shaped lingula and usually short not extending past vasiform orifice. Puparium has caudal furrow and a pair of caudal setae at the end. Subdorsum without compound pores and submarginal row of papillae absent. The result of puparium observation was photographed and used for making identification key in PDF format. Other literature study on the biological character and the whiteflies control technique are carried out to support comprehensive information for making the identification key. This identification key in PDF format can be used as a tool to identify A. dispersus and B. tabaci.